Edukasi dan Antisipasi Gurita dan Budaya Korupsi Melalui Sentuhan Kejiwaan dan Pendekatan Agama - Suaidi Suaidi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
Corruption is an unlawful act that has an impact on material and state financial losses, and also has an impact on the obstruction of infrastructure development programs and the development of people's welfare. Constitutionally, the poverty felt by the people is the responsibility of the state, but with acts of corruption, people are forced to become poor so that people are neglected from the control and protection of the state. This means that acts and deeds of corruption are evil acts that must be a concern so that they do not occur and must receive maximum punishment, the people are also educated to view acts of corruption as a common enemy and a crime that cannot be tolerated. This study aims to provide guidelines so that acts of corruption can be minimized with various approaches, including through a religious approach.